The temporalities of policymaking: The case of HIV test-and-treat policy adoption in Zimbabwe - Moran,M; Skovdal,M; Mpandaguta,E; Maswera,R; Kadzura,N; Dzamatira,F; Nyamukapa,C; Gregson,S; Tlhajoane,M (Health & Place, 2019)
Despite calls for “rapid adoption” of global health policies and treatment guidelines; there is little understanding of the factors that help accelerate their adoption and implementation. Drawing on in-depth interviews with sixteen Zimbabwean policymakers, we unpack how different factors, rhythmic experiences and epochal practices come together to shape the speeding up and slowing down of test-and-treat implementation in Zimbabwe. We present an empirically derived framework for the temporal analysis of policy adoption and argue that such analysis can help highlight the multiple and messy realities of policy adoption and implementation - supporting future calls for ‘rapid’ policy adoption.